Ab initio quantum dynamical study of the multi-state nonadiabatic photodissociation of pyrrole - Faraji, Shirin; Vazdar, M.; Reddy, V. Sivaranjana; Eckert-Maksic, M.; Lischka, H.; Köppel, Horst (The journal of chemical physics, 2011)
There has been a substantial amount of theoretical investigations on the photodynamics of pyrrole, often relying on surface hopping techniques or, if fully quantal, confining the study to the lowest two or three singlet states. In this study we extend ab initio based quantum dynamical investigations to cover simultaneously the lowest five singlet states, two π − σ* and two π − π* excited states. The underlying potential energy surfaces are obtained from large-scale MRCI ab initio computations. These are used to extract linear and quadratic vibronic coupling constants employing the corresponding coupling models. For the - N-H - N-H - stretching mode Q24 an anharmonic treatment is necessary and also adopted. The results reveal a sub-picosecond internal conversion from the S4 (π − π*) state, corresponding to the strongly dipole-allowed transition, to the S1 and S2 (π − σ*) states and, hence, to the ground state of pyrrole. The significance of the various vibrational modes and coupling terms is assessed. Results are also presented for the dissociation probabilities on the three lowest electronic states.
Gesehen am 03.05.2022